Pyogenic hepatic abscess induced secondary to toothpick penetration of stomach - Chou, Dev-Aur; Hung, Min-Chang; Lai, Ji-Ching; Huang, Wayne Shih-Wei (Turkish Journal of Gastroenterology, 2018)
Abstract Cite this article as: Chou DA, Hung MC, Lai JC, Huang WSW. Pyogenic hepatic abscess induced secondary to toothpick penetration of stomach. Turk J Gastroenterol 2018; 29: 241-2.